STRATEGI ADAPTASI SOSIAL KELUARGA MISKIN DALAM MENGHADAPI PANDEMI : ANALISIS KETAHANAN SOSIAL - YOHANIS NAFLY SELFANYA; ILDI AGUSTINA FINCE SARIWATING; PETRUS PARETY; YOSIAS MAOLLO; YOSPATER HENDY PROIM (JURNAL BADATI, 2022)
The COVID-19 pandemic has significantly impacted society, particularly poor families who face greater challenges in maintaining their survival. This study aims to analyze the social adaptation strategies developed by poor families in facing the pandemic and identify factors influencing their social resilience. Using a systematic literature review method, this study analyzed 47 articles published between January 2020 and December 2023. The results identified six main adaptation strategies: income diversification (68%), social capital utilization (62%), expenditure reduction (85%), aid program utilization (73%), digital adaptation (45%), and residential relocation (28%). The effectiveness of adaptation strategies is influenced by internal factors (family characteristics) and external factors (system support). Social capital proved to be a crucial element in supporting poor families' resilience, although social restrictions during the pandemic presented new challenges in building and maintaining social networks. This study recommends developing comprehensive social protection programs, strengthening the digital capacity of poor families, and facilitating community social capital development to enhance the social resilience of poor families in facing crises.